Keberagaman Dewan Direksi terhadap Struktur Modal - Lailatul Fitri; Vera Noviana Erlita (Trunojoyo University of Madura, 2018)
The characteristics of the board in a company affect the company's capital structure because of the relationship between the monitoring mechanism which is a function of the board of directors on the company's capital structure. The purpose of this study was to determine the effect of the board of directors' diversity which is proxied on the variables of female presence, foreign citizenship, board size, sales growth, profitability and firm size on capital structure. This study uses quantitative methods using multiple linear regression methods. The sample of this study is a manufacturing company listing on the Indonesia Stock Exchange for the period of 2016 - 2017. The method used to determine the sample is purposive sampling. This research data can be obtained from secondary data, namely the company's annual report. The results of hypothesis testing using multiple linear regression showed that the presence of women and foreign citizenship had an effect while the variable board size, sales growth, profitability and firm size did not affect the capital structure.